2007
DOI: 10.1016/j.jneuroim.2006.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Mice deficient in the ALS2 gene exhibit lymphopenia and abnormal hematopietic function

Abstract: One form of juvenile onset autosomal recessive amyotrophic lateral sclerosis (ALS2) has been linked to the dysfunction of the ALS2 gene. The ALS2 gene is expressed in lymphoblasts, however, whether ALS2-deficiency affects periphery blood is unclear. Here we report that ALS2 knockout (ALS2 −/− ) mice developed peripheral lymphopenia but had higher proportions of hematopoietic stem and progenitor cells in which the stem cell factor-induced cell proliferation was up-regulated. Our findings reveal a novel function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…These deficits were not noted in all the reported mice, but similar discrepancies in behavioral phenotyping have been noted in mice derived from different 129 strains [34,35]. Additionally, we reported that ALS2 −/− mice develop peripheral lymphopenia and had higher proportions of hematopoietic stem and progenitor cells in which the stem cell factor-induced cell proliferation was up-regulated [36]. A direct link between ALS and the lymphohematopoietic system comes from clinical observations that ALS patients had marked lymphopenia with reductions in CD2 + and CD8 + T cells in comparison to age-matched controls [37].…”
Section: Als2 Knockout Micesupporting
confidence: 69%
“…These deficits were not noted in all the reported mice, but similar discrepancies in behavioral phenotyping have been noted in mice derived from different 129 strains [34,35]. Additionally, we reported that ALS2 −/− mice develop peripheral lymphopenia and had higher proportions of hematopoietic stem and progenitor cells in which the stem cell factor-induced cell proliferation was up-regulated [36]. A direct link between ALS and the lymphohematopoietic system comes from clinical observations that ALS patients had marked lymphopenia with reductions in CD2 + and CD8 + T cells in comparison to age-matched controls [37].…”
Section: Als2 Knockout Micesupporting
confidence: 69%
“…Alternative therapeutic strategies based on the modulation of adult neurogenesis have been already proposed and appeared promising for other neurodegenerative diseases, such as Parkinson disease (PD) 94. Few data on this specific issue have been published in ALS models, but there is convincing evidence of widespread regenerative response, mainly toward glia, in the spinal cord of tgSOD-1 mice 127. Moreover, a temporal and regional plasticity of NPs in the dorsal horns of the spinal cord, as well as in motor cortex and lateral ventricle, in conjunction with their differentiation into neuron-like cells in response to MN loss, has been described during the disease onset or progression stages 128.…”
Section: Innovative Sc Therapies Beyond Replacement: Neuroprotection mentioning
confidence: 99%
“…Deletion of ALS2 GEF impeded mice leukocyte extravasation into blood citculation (Erie et al, 2007). Similarly ALS patients with mutated ALS2 gene suffered from lymphopenia, condition associaetd with reduced levels of circulating leukocytes (Provinciali et al, 1988).…”
Section: Integrin αLβ2 Endocytosis and Its Association With Hrab5cmentioning
confidence: 99%